Difficulties in diagnosing primary cutaneous mucormycosis: Excluding mycobacterium other than tuberculosis - Indah, Chinda Liaska; Menaldi, Sri Linuwih Susetyo Wardhani; Sirait, Sondang Pandjaitan; Widaty, Sandra (UI Scholars Hub, 2025)
Background: Mucormycosis is a rare fungal infection caused by a group of opportunistic fungi from the class Zygomycetes. Primary cutaneous mucormycosis is the most common type of mucormycosis in immunocompetent patients. This study reported a case of primary cutaneous mucormycosis with nonspecific clinical characteristics and various supporting examinations. The patient was successfully treated with in toto excision and oral ketoconazole. Case Illustration: A 40-year-old female presented with purplish-red spots and painless lumps on the second finger of her right hand, which had been present for a year. She had a history of frequent fish tank cleaning and gardening but denied any known injury. Physical examination revealed multiple well-circumscribed and confluent erythematous-violaceous plaques and nodules. An in toto excisional biopsy was performed for histopathological examination, culture, and a rapid molecular test (RMT) using the Xpert MTB/RIF® test (Cepheid, USA). Histopathological examination revealed granulomatous suppurative inflammation, and fungal culture revealed growth of Mucor species. Discussion: Clinical findings in cutaneous mucormycosis are nonspecific. The diagnosis is confirmed by identifying the organism through biopsy and histopathological examination, as well as culture. Histopathology will reveal granulomas in the dermis and subcutis containing numerous macrophages and Langhans giant cells, often with phagocytosed fungal elements. Fungal culture yields positive results in 72–89% of cases of skin mucormycosis conducted on Sabouraud and potato dextrose agar media. Conclusion: This case emphasizes the need for broad differential consideration and thorough diagnostic workup in nonspecific cutaneous mucormycosis and supports surgical excision with systemic antifungal therapy for chronic, localized primary disease.